2020
DOI: 10.1089/neu.2019.6581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frailty on Outcome after Traumatic Spinal Cord Injury

Abstract: Frailty negatively affects outcome in elective spine surgery populations. This study sought to determine the effect of frailty on patient outcome after traumatic spinal cord injury (tSCI). Patients with tSCI were identified from our prospectively collected database from 2004 to 2016. We examined effect of patient age, admission Total Motor Score (TMS), and Modified Frailty Index (mFI) on adverse events (AEs), acute length of stay (LOS), in-hospital mortality, and discharge destination (home vs. other). Subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Our study confirms these findings, and multivariate analysis revealed increased total hospital costs following surgery in obese patients receiving anterior TL fusion for burst fractures compared to patients with BMIs less than 30. Similarly, patient frailty has been validated as an independent predictor of postoperative complications in several previous studies, and our findings confirm these associations in both patients with scoliosis and burst fractures [45][46][47][48][49][50]. In those patients with scoliosis and burst fractures, frailty was shown to increase the total inpatient LOS non-frail patients.…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirms these findings, and multivariate analysis revealed increased total hospital costs following surgery in obese patients receiving anterior TL fusion for burst fractures compared to patients with BMIs less than 30. Similarly, patient frailty has been validated as an independent predictor of postoperative complications in several previous studies, and our findings confirm these associations in both patients with scoliosis and burst fractures [45][46][47][48][49][50]. In those patients with scoliosis and burst fractures, frailty was shown to increase the total inpatient LOS non-frail patients.…”
Section: Discussionsupporting
confidence: 90%
“…This effect is not linear, as demonstrated by the margins of interaction between age (by decade) and categorical level of frailty (see Figure 1). This effect (for readmission, reoperation, length of stay, and discharge to non-home destination) begins after the age of 60, which is in line with previously reported studies [32,34,35]. The mCCI proved a significant predictor of all adverse events on univariate and multivariable analysis, and the effect size remained similar for both.…”
Section: Discussionsupporting
confidence: 89%
“…The suggested mechanism for this discrepancy has traditionally been the burden of age-related co-morbidities influencing clinical outcomes and reduction of physiological reserve, which has been manifested as measures of frailty or frailty indices in recent years. This hypothesis has been further substantiated with the correlation of worsening frailty to increased complication rate after spine surgery, and poorer recovery after spinal cord injury [28,34,35]. However, despite DCM being the most common indication for cervical spine surgery in North America, the effect of frailty on the outcomes after DCM surgery has not been investigated [16].…”
Section: Discussionmentioning
confidence: 99%
“…ostensibly play more of a role in the determinant of peri-operative risk. This concept of frailty, and its association with the assessment of surgical risk, is emerging as an important tool for surgical decision making and has been a recent focus of interest in pathologies such as spinal cord injury and adult deformity surgery [51,52,53]. However, the impact of frailty on the outcomes from DCM appears to be less well defined.…”
Section: Discussionmentioning
confidence: 99%